Patient Safety: Break the Silence - Johnson, Hope L.; Kimsey, Diane (AORN journal, 2012)
A culture of patient safety requires commitment and full participation from all staff members. In 2008, results of a culture of patient safety survey conducted in the perioperative division of the Lehigh Valley Health Network in Pennsylvania revealed a lack of patient-centered focus, teamwork, and positive communication. As a result, perioperative leaders assembled a multidisciplinary team that designed a safety training program focusing on Crew Resource Management, TeamSTEPPS, and communication techniques. The team used video vignettes and an audience response system to engage learners and promote participation. Topics included using preprocedural briefings and postprocedural debriefings, conflict resolution, and assertiveness techniques. Postcourse evaluations showed that the majority of respondents believed they were better able to question the decisions or actions of someone with more authority. The facility has experienced a marked decrease in the number of incidents requiring a root cause analysis since the program was conducted.